ПОРІВНЯННЯ ЕФЕКТИВНОСТІ ЗГЛАДЖУВАННЯ СИГНАЛІВ НАПРУГИ НА ПЛАЗМОЕРОЗІЙНОМУ НАВАНТАЖЕННІ ТА СТРУМУ В НЬОМУ БАГАТОІТЕРАЦІЙНИМИ МЕТОДАМИ ФІЛЬТРАЦІЇ - Шидловська , Н.А.; Захарченко, С.М.; Черкаський, О.П. (Інститут електродинаміки НАН України, Київ, 2017)
Characterized signals of voltage on the multichannel plasma-erosive load and its current, as a result of capacitor discharge on it in general. The influence of parameters of elements of the discharge circuit and the initial conditions for them in the transition process in plasma-erosive load and a factor of stochastic amplitude modulation of the discharge current and voltage at the load are considered. A critical analysis of the signal filtering methods is given. Described filtering of signals voltage on plasma-erosive load and its current by method of their partially recovery by their incomplete mode decomposition. The algorithm of new multi-iterative method of moving average with increasing width of the filtering window of non-stationary non-periodic signals is described. The comparative analysis of efficiency of filtration of signals of voltage on plasma-erosive load and its current by a new method and a method of their partially recovery by their incomplete mode decomposition is given. References 22, figures 5, tables 2.